(3QSGdI aj GdGSJYGQGJs - (3GdbhTLj, Ydj Hf eMeO, J(B879(3g`s ((3YHO Gddg Hf HTjQ GdHhSfhjs)
(3ChdgG (B:s
(3GdMeO ddg Pj Gdef hGdEMSGf hGddg CYde Cf GddaX GdehVhY GdeSJYed eaQOG cGf Ch eQcHG Cf GSJYed ajeG hVY dg aMbjbI (B: (3eKGd GdMbjbI aj GdeaQO cGdCSO aj GdMjhGfs
(3BNQgG (B:s
(3haj GdYHGOI eLGR cPdc haj GdTQY HGdYcS Cj MbjbI TQYjI aj GdYHGOI heLGR TQYj aj GdOYGA dCf hUag aj GddZI ddOYGA haj GdTQY ddYHGOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B: 5 / 9s
(3eYLe GdeDdajf(B: 2 / 522s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs